Flavonoids and anxiety: decoding their role in brain function and pathophysiology - Riya Singla; Sonia Kamboj; Brijesh Kumar Duvey; Anurag Bhargava; Jasmine Chaudhary (Medicine in Drug Discovery)
Anxiety disorder ranks among the most common mental health issues globally, thereby emphasizing the pressing necessity for the development of safer and more effective treatment alternatives. A noteworthy class of compounds in this context is flavonoids, which are naturally polyphenolic substances found in abundance within fruits, vegetables, and various medicinal plants. These compounds have garnered attention as candidates for the modulation of behaviours associated with anxiety. Examining the neurological mechanisms that underlie the anxiolytic effects of flavonoids reveals significant interaction with essential neurotransmitter systems. Specifically, engagement with serotonergic and dopaminergic pathways has been observed, indicating the multifaceted nature of flavonoids’ influence on anxiety responses. The biological activities, including antioxidant, anti-inflammatory properties, contribute to an additional layer to the potential therapeutic effect. Therefore, this review mainly focuses on the pathological facets of anxiety and explores the possible mechanism of flavonoids with the preclinical and clinical aspects for curing anxiety. Moreover, a growing body of experimental and clinical evidence indicates that certain flavonoids, including apigenin, quercetin, and luteolin, possess a considerable capacity to mitigate symptoms of anxiety, frequently resulting in a reduced incidence of adverse effects relative to traditional pharmacological therapies. This body of work reinforces the proposition that flavonoids may serve as viable natural alternatives to supplementary treatments in the management of anxiety disorders. Nevertheless, it remains imperative that additional research is conducted to clarify the mechanisms underlying the pharmacological effects of these flavonoids. Furthermore, investigations aimed at optimizing their bioavailability and validating clinical efficacy through extensive human trials are essential to fully ascertain their therapeutic potential in anxiety management.